Teacher Education in Times of Change - Beauchamp, Gary; Clarke, Linda; Hulme, Moira; Jephcote, Martin; Kennedy, Aileen; Magennis, Geraldine; Menter, Ian; Murray, Jean; Mutton, Trevor; O'Doherty, Teresa; Peiser, Gillian (Policy Press, 2015)
Why is teacher education policy significant - politically, sociologically and educationally? While the importance of practice in teacher education has long been recognised, the significance of policy has only been fully appreciated more recently. Teacher education in times of change offers a critical examination of teacher education policy in the UK and Ireland over the past three decades, since the first intervention of government in the curriculum. Written by a research group from five countries, it makes international comparisons, and covers broader developments in professional learning, to place these key issues and lessons in a wider context.